Tag det som en mand! Metaforik og maskulinitet i autopatografier om kræft - Hvidtfeldt, Karen; Krogh Hansen, Per (K&K - Kultur og Klasse, 2021)
While serious illness is a crisis in the life course of any human being, it harmonizes particularly poorly with traditional notions of masculinity. Statistically, more men than women get cancer, but women seem more likely to communicate about their emotions and experiences of illness in public. In this article, we examine the connection between cancer narratives, war and combat metaphors and hegemonic masculinity based on six recent Danish autobiographies written by men about their experience of having cancer. Based within critical masculinity theories and metaphor theory, we examine how the autobiographies apply and develop traditional combat metaphors and we argue that new narratives and (counter) metaphors are developed and that they influence both the experience of illness and the understanding of masculinity.